Pharmacological treatments for fatigue associated with palliative care: executive summary of a Cochrane Collaboration systematic review. Issue 1 (10th February 2016) - Mücke, Martin; Mochamat,; Cuhls, Henning; Peuckmann‐Post, Vera; Minton, Ollie; Stone, Patrick; Radbruch, Lukas
Abstract: Background: In palliative care patients, fatigue can be severely debilitating and is often not counteracted with rest, thereby impacting daily activity and quality of life. Further complicating issues are the multidimensionality, subjective nature and lack of a consensus definition of fatigue. The review aimed to evaluate the efficacy of pharmacological treatments for fatigue in palliative care, with a focus on patients at an advanced stage of disease, including patients with cancer and other chronic diseases. Methods: We considered randomized controlled trials concerning adult palliative care with a focus on pharmacological treatment of fatigue compared with placebo, application of two drugs, usual care or a non‐pharmacological intervention. The primary outcome had to be non‐specific fatigue (or related terms such as asthenia). We searched the CENTRAL, MEDLINE, PsycINFO and EMBASE, and a selection of cancer journals up to 28 April 2014. Two review authors independently assessed trial quality and extracted the data. Results: We screened 1645 publications of which 45 met the inclusion criteria. In total, we analysed data from 18 drugs and 4696 participants. There was a very high degree of statistical and clinical heterogeneity in the trials. Meta‐analysis of data was possible for modafinil, pemoline, and methylphenidate. Conclusions: Due to the limited evidence, we cannot recommend a specific drug for the treatment of fatigue in palliative care patients. Some drugs, which may be beneficial for the treatment of fatigue associated with palliative care such as amantadine, methylphenidate, and modafinil, should be further researched.